2018
DOI: 10.12659/msm.911333
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor (EGFR) Mutations and Anaplastic Lymphoma Kinase/Oncogene or C-Ros Oncogene 1 (ALK/ROS1) Fusions Inflict Non-Small Cell Lung Cancer (NSCLC) Female Patients Older Than 60 Years of Age

Abstract: BackgroundLung cancer has become a leading disease for the tumor-induced mortality. Non-small cell lung cancer (NSCLC) accounts for approximately 80% of all lung cancers. The present research aimed to evaluate the correlation between the anaplastic lymphoma kinase/oncogene or c-ros oncogene 1 (ALK/ROS1) fusions or mutations of epidermal growth factor receptor (EGFR) and ages or gender of patients.Material/MethodsAmong 1449 NSCLC patients, 457 patients who were diagnosed as consecutive EGFR mutations or ALK/ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
2
7
1
Order By: Relevance
“…Consistently, we observed such correlation in our study, indicating that the high frequency of KRAS mutation in our cohort could be attributable to high prevalence of smoking in Vietnam population. In addition, we found that ALK and ROS1 rearrangement mutations were more common in younger patients as compared to elderly patients, which is consistent with previous studies 28,29 . Take together, our data revealed several significant correlations between driver gene mutation prevalence and patients' clinical characteristics.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently, we observed such correlation in our study, indicating that the high frequency of KRAS mutation in our cohort could be attributable to high prevalence of smoking in Vietnam population. In addition, we found that ALK and ROS1 rearrangement mutations were more common in younger patients as compared to elderly patients, which is consistent with previous studies 28,29 . Take together, our data revealed several significant correlations between driver gene mutation prevalence and patients' clinical characteristics.…”
Section: Discussionsupporting
confidence: 92%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Correlation between mutation prevalence and clinicopathological features of Vietnamese NSCLC patients. Previous studies have reported significant association between prevalence of driver mutations and patients' clinicopathological features [24][25][26][27][28][29] . However, the results are often inconsistent across different studies.…”
Section: Comparison Of Mutation Profiles Among Three Nsclc Cohorts Tmentioning
confidence: 99%
“…In addition, recent studies showed that 69% and 65.8% were male patients (9,11). Ke et al reported that the percentage of women was significantly higher in patients younger than 60 years compared to those older than 60 years (28). In our study, 84 (65.1%) of the 129 patients were female.…”
Section: Discussionsupporting
confidence: 58%
“…Resistance to therapy is a major clinical issue contributing to poor prognosis [2]. Non-small-cell lung cancer (NSCLC) accounts for approximately 80-85% of all lung cancers [3,4]. In 2016, Sweden recorded 4108 new lung cancer cases; 3677 patients died from the disease in that year [5,6].…”
Section: Introductionmentioning
confidence: 99%